On a stability of thin microperiodic plates - Jędrysiak, Jarosław (Wydawnictwo Politechniki Łódzkiej, 1997)
The structural macromechanics is applied to investigate the stability of a composite plate. Thin elastic plates with microperiodic structure in planes parallel to the midplane are examined. A new retined approach is used to the problem of the dynamic stability of periodic plates. Some special results are shown
Keywords: cienkie płytki mikroperiodowe; stabilność dynamiczna; makromechanika strukturalna; płyta okresowa; dynamic stability; thin microperiodic plates; structural macromechanics; periodic plate